Studying the Effect of Changing the Outer Diameter of the Transmitter Coil on the Performance of Wireless Power Transfer System used for Medical Purposes for Devices Implanted inside the Human Body - Omran اللاله عبد القادر الأمير; Abulaweenat محمد مسعود (Journal of Pure & Applied Sciences, 2021)
The efficiency and ability of transferring power or electrical energy in a wireless power transmission system from one point to another depends mainly on the operating frequency and the type, shape and dimensions of the coils used as the coils play the greatest role in linking the magnetic flux between the transmitting and receiving points. This paper aimed to study the effect of changing the outer diameter of the transmission coil on the performance of an energy transmission system used for medical purposes for devices implanted inside the human body through a simulation of the system's performance using the Matlab language. The obtained results showed the direct and effective effect of changing the outer diameter of the transmitting coil on the mutual inductance, coupling coefficient, the transferred power to the load, the specific absorption rate SAR, as well as the efficiency of the system. The results showed that the greater the outer diameter of the transmitting coil compared to the outer diameter of the receiving coil the lower the mutual inductance, the lower the coupling coefficient, the transformed power, and the SAR absorption rate. In all cases, the specific absorption rate did not exceed the permissible limits.